2011
DOI: 10.1007/s12013-011-9203-7
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Fast-Track Clinical Pathway Decreases Postoperative Length of Stay and Hospital Charges for Liver Resection

Abstract: A fast-track clinical pathway is designed to streamline patient care delivery and maximize cost effectiveness. It has decreased postoperative length of stay (LOS) and hospital charges for many surgical procedures. However, data on clinical pathways after liver surgery are sparse. This study examined whether use of a fast-track clinical pathway for patients undergoing elective liver resection affected postoperative LOS and hospital charges. A fast-track clinical pathway was developed and implemented by a multid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
104
2
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(117 citation statements)
references
References 20 publications
6
104
2
5
Order By: Relevance
“…In this study, both the postoperative hospital stay and total hospital stay after pathway implementation are found to be significantly shorter than those of the non-CP group. The mean LOHS for hepatectomy in our study is 8.3 days in the CP group, which is similar to that in a recent singlecentre study in China (Lin et al, 2011). Recently, it was evident that perioperative comprehensive supportive care interventions, including health education, psychological support and stress management, were associated with a shorter LOHS in patients with esophageal carcinoma (Zhang et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, both the postoperative hospital stay and total hospital stay after pathway implementation are found to be significantly shorter than those of the non-CP group. The mean LOHS for hepatectomy in our study is 8.3 days in the CP group, which is similar to that in a recent singlecentre study in China (Lin et al, 2011). Recently, it was evident that perioperative comprehensive supportive care interventions, including health education, psychological support and stress management, were associated with a shorter LOHS in patients with esophageal carcinoma (Zhang et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…There are notable differences between the present study and the former report with regard to discharge exercises. For instance, Lin et al (13) reported that a postoperative length of stay of 6 days was ideal, and considered discharge before this time to be too early. It is difficult to confirm in a retrospective study if discharge was premature; however, it should be noted that the same discharge criteria were maintained throughout this study.…”
Section: Discussionmentioning
confidence: 99%
“…Elements include minimal preoperative bowel preparation and fasting, admission on the day of surgery, aggressive early ambulation, strict analgesia protocols, early postoperative introduction of oral fluids and food, and minimal use of drips and drains. These pathways are safe, feasible and reduce complication rates and LOS across all types of abdominal surgery (Adamina et al 2011, Cerantola et al 2013, Coolsen et al 2013, Li et al 2012, Lin et al 2011, Varadhan et al 2010, Wijk et al 2014.…”
Section: Diagnostic Factorsmentioning
confidence: 99%